Disentangling the taxonomy of Belostoma Latreille (Hemiptera: Belostomatidae) with the aid of DNA barcoding approaches. Issue 3 (5th May 2021) - Gauterio, Thaísa B; Ribeiro, José Ricardo I; Robe, Lizandra J; Ferrari, Augusto
Abstract: Belostoma is the most diverse genus of Belostomatidae, comprising 74 species. The small Belostoma species are challenging to identify mainly due to the presence of cryptic species. As DNA barcoding has been a crucial tool to solve the taxonomic impediment associated with many taxa, we compared species delimitations obtained by morphological and molecular approaches, in order to help to disentangle the taxonomy of Belostoma . We sampled 192 specimens of Belostoma across the Rio Grande do Sul Brazilian Coastal Plain. Specimens were first identified with the use of morphological markers and then characterized for two mitochondrial markers: cytochrome C oxidase subunit I (COI) and 16S rRNA genes, generating 181 and 164 sequences, respectively. These were complemented with Belostoma sequences downloaded from NCBI/BOLD (101 for COI & 13 for 16S). Thus, matrixes including 282, 177 and 299 sequences for COI, 16S and the concatenated data set, respectively, were analysed through phylogenetic, phylogeographic and distance approaches. The initial morphological evaluation allowed the identification of 14 male genitalia morphotypes, whose sequences were added to a preliminary matrix containing ​NCBI/BOLD sequences of five other described species, allowing us to recover 10 clades in the molecular analyses. Patterns of reciprocal monophyly were confirmed for only six of the studied species: Belostoma angustum, Belostoma cummingsi, Belostoma dentatum, Belostoma noualhieri, Belostoma orbiculatum and B elostoma ribeiroi . Belostoma candidulum, Belostoma horvathi and Belostoma sanctulum appeared intermingled in a single clade. The grouping of these with the other five distinct (male genital) morphotypes reveals a clade with high levels of morphological polymorphism or phenotypic plasticity.